Assessment of Brazilian pharmacists’ knowledge about antimicrobial resistance - Fernando de Sa Del Fiol; Silvio Barberato-Filho; Luciane Cruz Lopes; Cristiane da Cassia Bergamaschi; Rodrigo Boscariol (Journal of Infection in Developing Countries)
Introduction: Antimicrobial resistance (AR) is a multifaceted problem of global significance. In addition to developing new drugs and using antimicrobial guidelines, it is essential that health professionals understand all aspects of the problem and the most effective ways to handle it. This study evaluated pharmacists’ level of knowledge about bacterial resistance and antibiotic use in Brazil. Methodology: The study was conducted using a survey provided electronically to pharmacists in São Paulo State, Brazil. Results: In total, 754 pharmacists completed the survey. The majority of the pharmacists were young (under 30 years of age), female, and worked in community pharmacies. Pharmacists who worked in hospital or community pharmacies reported a greater AR interference in their work than did pharmacists working in other locations (p < 0.05). With respect to factors that contribute to AR, pharmacists placed little weight on the role of inadequate hand washing or lack of immunization campaigns. The pharmacists also believed that vaccination was of limited value in combating AR and instead placed the highest value on educational campaigns. The study showed that pharmacists who used package inserts and advertising material as their source for updated information had a poorer understanding of the appropriate use of antibiotics than did those who obtained their information from scientific journals, textbooks, or scientific meetings. Conclusions: The results highlight the need for adequate information regarding AR to reach health professionals such as pharmacists. Governments should promote campaigns for integrated actions to combat the serious global problem presented by AR.